Intermittent lighting improves resilience of broilers during the peak phase of sub-clinical necrotic enteritis infection. (3rd November 2017) - Rodrigues, I; Svihus, B; Bedford, M R; Gous, R; Choct, M
Abstract: Necrotic enteritis, either in its clinical or sub-clinical form is known to cause massive economic losses in the broiler chicken industry. Currently, the use of in-feed antibiotics as growth promoters is discouraged. Therefore, mechanisms to control NE through diet include reduction of digesta viscosity, promotion of lower pH in the gastrointestinal tract (GIT) through acidification of feed, production of short-chain fatty acids and overall stimulation of beneficial bacteria growth. Intermittent lighting programs increase feed retention in the crop and reduce pH in the foregut compartments in comparison with standard commercial lighting programs and therefore may be a valuable, yet underexploited, barrier to prevent the invasion of the GIT by pathogens. In this experiment, a 2 × 2 factorial arrangement of treatments was employed in a randomized design to investigate whether intermittent lighting would increase broiler resilience to sub-clinical necrotic enteritis. A total of 390 Cobb 500 same-hatch, mixed sex, day-old chicks were assigned to 30 floor pens to test the effect of 2 factors, namely, lighting schedule (continuous, 18L:6D vs. intermittent, 1L:3D:1L:3D:1L:3D:1L:3D:2L:6D) and a sub-clinical necrotic enteritis challenge (challenge vs. no challenge). Challenged birds had lower feed intake and weight gain and poorer feed conversion ratio (FCR; P < 0.005). Intermittent lighting reduced feed intake ( P < 0.05) without compromising final body weight gain. During the peak phase of Clostridium perfringens Type A infection, the negative impact of the disease challenge on feed efficiency was lower for animals under intermittent lighting than for those under a 18L:6D schedule (2-way interaction, P < 0.005). Thus, in flocks that are raised under antibiotic-free production systems, intermittent lighting programs applied at least during the critical period for necrotic enteritis risks, i.e., d 18–24, may be a practical, non-medicated way to increase resilience of broilers to this disease.